Perbandingan Fraksi Trombosit Imatur (IPF) dan Prokalsitonin (PCT) sebagai Penanda Biologis Tingkat Keparahan Infeksi dalam Hubungannya dengan Antigen NS1 pada Pasien Demam Berdarah Dengue (DBD) - Baihaki, Ichwan; -, Mutmainnah; Nugroho, Heru Purwanto; Aprilicia, Gita (Cermin Dunia Kedokteran, 2026)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus (DENV) and transmitted by the Aedes aegypti and Aedes albopictus mosquito vectors. This disease remains a major global health problem, particularly in tropical regions such as Indonesia. Clinical indicators of DHF severity include thrombocytopenia and shock, which are associated with high viremia levels and an increase in dengue NS1 antigen in the vascular system. This study compares immature platelet fraction (IPF) and procalcitonin (PCT) levels as biomarkers of infection severity in relation to DENV NS1 antigen positivity. Methods: This study included 35 patients with DHF and 35 healthy controls. IPF values and PCT levels were measured. Differences between the two groups were analyzed using an independent t-test. Results: p-values for both IPF and PCT were < 0.05, indicating statistically significant differences between DHF patients and healthy controls. These findings suggest that higher IPF values are associated with thrombocytopenia, whereas elevated PCT levels may reflect more severe infection, including dengue shock syndrome. Conclusion: There are significant differences in IPF and PCT levels between DHF patients and controls, depending on dengue NS1 antigen positivity. IPF may serve as an indicator of thrombocytopenia, while PCT may be a marker of infection severity, including dengue shock syndrome, in patients with dengue hemorrhagic fever.